Propuesta didáctica interdisciplinar en torno a las costumbres, ritos y tradiciones de las cigarreras, como ejemplo del patrimonio inmaterial de la cultura hispánica - Bobadilla Pérez, María (Huarte de San Juan. Filología y Didáctica de la Lengua, 2016)
This article analyses the Spanish figure of the cigarrera, female cigar maker, as a referent within the intangible heritage of the Spanish culture. The community of the factory cigar makers has been so deeply rooted in our cultural identity that its customs, rituals and traditions have inspired musicians, writers, painters and even film makers since the nineteenth century. We initially present an analysis of the traditions and rituals of the factory workers of the Galician city of A Coruña as represented in Emilia Pardo Bazán’s La Tribuna (1883). Afterwards, we discuss the use of this novel as an interdisciplinary resource in the Secondary School classroom in an educational and cultural project where the main aim is to help students recognise and value the transcendence of the cigar maker community in our collective imagination.
Keywords: Female cigar maker; intangible heritage; traspodidactics; La Tribuna